PERUBAHAN KONSEPSI SISWA SD PADA MATERI SIFAT-SIFAT CAHAYA MELALUI PEMBELAJARAN EXPERIENTIAL LEARNING - Alamanda, Gilang Camilla (2017)
This study aims to find students' conceptual change on the nature of lights lesson through experiential learning. The method used was quasi-experimental with pre-test post-test control group design. Subject of this study are 62 students in fifth grade of primary school which consist of 31 students at experimental group and 31 students at control group. The instrument used is a test of understanding of concepts, observations of learning implementation, attitude scale questionnaire. The experimental group applied experiential learning model, while the control group applied learning without experiential learning model. The results shows that there was significant change of student conception between the experimental group and the control group seen from the result of the N-gain t test that is 0,00 with the average of N-gain experimental group 0,6 and the control group that is 0.2. So it can be concluded that the experiential learning model of Experiential Learning gives the impact of changes in student conceptions in the experimental group compared with the control group.------ Penelitian ini bertujuan untuk mengetahui perubahan konsepsi siswa SD pada materi sifat-sifat cahaya melalui pembelejaran Experiential Learning. Metode yang digunakan dalam penelitian ini adalah kuasi eksperimen dengan desain pre-test post-test control group design. Subjek penelitian ini yaitu 62 siswa di kelas 5 sekolah dasar yang terdiri dari 31 siswa kelompok eksperimen dan 31 siswa kelompok kontrol. Instrumen yang digunakan terdiri dari tes pemahaman konsep, lembar keterlaksanaan model Experiential Learning, dan lembar angket sikap siswa. kelompok eksperimen menerapkan model pembelajaran Experiential Learning, sedangkan kelompok kontrol tanpa menerapkan pembelajaran Experiential Learning. Hasil penelitian menunjukkan bahwa terjadi perubahan konsepsi siswa yang signifikan antara kelompok eksperimen dan kelompok kontrol yang terlihat dari hasil uji t N-gain yaitu 0,00 dengan rata-rata N-gain lelompok eksperimen 0,6 dan kelompok kontrol yaitu 0,2. Jadi dapat disimpulkan bahwa model pembelajaran Experiential Learning memberikan dampak perubahan konsepsi siswa pada kelompok eksperimen dibandingkan dengan kelompok kontrol.